2012
DOI: 10.1002/jsfa.5736
|View full text |Cite
|
Sign up to set email alerts
|

Environmental analysis of the logistics of agricultural products from roof top greenhouses in Mediterranean urban areas

Abstract: The RTG may become a strategic factor in the design of low-carbon cities in Mediterranean areas. Short-term implementation in the city of Barcelona could result in savings of 66.1 tonnes of CO₂ eq. ha(-1) when considering the global warming potential, and of 71.03 t ha(-1) when considering that the transformation from woodland to agricultural land is avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 22 publications
0
63
0
Order By: Relevance
“…Most agreed that urban agriculture can have positive effects in the following areas: environmental improvement, education, job creation, leisure activity option diversification, community building, and societal views of agriculture. Although these effects have not yet been studied in Berlin, perceptions of positive impacts are reported in other studies that describe similar urban agriculture impacts elsewhere (Anthopoulou et al 2013;Caplow 2009;Eigenbrod and Gruda 2014;Pourias et al 2015;Sanyé-Mengual et al 2013;Specht et al 2014). It is likely that urban agriculture can similarly offer social and environmental benefits in Berlin.…”
Section: Perceptions Of Urban Agriculture Impactsmentioning
confidence: 72%
See 2 more Smart Citations
“…Most agreed that urban agriculture can have positive effects in the following areas: environmental improvement, education, job creation, leisure activity option diversification, community building, and societal views of agriculture. Although these effects have not yet been studied in Berlin, perceptions of positive impacts are reported in other studies that describe similar urban agriculture impacts elsewhere (Anthopoulou et al 2013;Caplow 2009;Eigenbrod and Gruda 2014;Pourias et al 2015;Sanyé-Mengual et al 2013;Specht et al 2014). It is likely that urban agriculture can similarly offer social and environmental benefits in Berlin.…”
Section: Perceptions Of Urban Agriculture Impactsmentioning
confidence: 72%
“…According to Lohrberg and Timpe (2012), the definitions and aims of urban agriculture are multiple and diverse. Beyond food production, urban agriculture provides environmental and social services and supports local economies by a significant direct urban market orientation (Sanyé-Mengual 2015). In the past, urban agriculture has often been discussed as a solution to the global challenges posed by urban population growth and climate change (Despommier 2010;De Zeeuw et al 2011;FAO 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerón-Palma et al [15] investigate the barriers and opportunities that technical focus groups (e.g., architects, engineers) associate with implementing Rooftop Greenhouses in the Mediterranean region. Previous studies of large European cities have investigated the potential for rooftop greenhouses in Barcelona (Spain) [15,[30][31][32], rooftop farming in London (UK) [33], and large-scale urban agriculture in the Netherlands [34,35]. To date, no previous studies have focused on Germany, and no previous studies have reported on the introduction and innovation process of ZFarming from a stakeholder perspective.…”
Section: Zero-acreage Farmingmentioning
confidence: 99%
“…As for rooftop vegetables, the experimental data from Taylor et al (2012) of growing lettuce in a 19-m 2 net shack led to an estimate that if all of Manila's metropolitan area lettuces (1248 t annually) were supplied by roof hydroponics,~2000 t of CO 2 would be reduced through reduced food miles and air conditioning (from lowering building temperature). Sanyé-Mengual et al (2013) estimated that compared to conventional production methods for tomato production in Barcelona, Spain, a rooftop greenhouse system could save up to 74 % of the energy used for conventional farming. Orsini et al (2014) projected that if all the flat rooftop surfaces in Bologna, Italy, were converted into rooftop gardens, it could result in the annual capture of about 624 t of CO 2 .…”
Section: Introductionmentioning
confidence: 99%